Creativity and disruptive innovation in entrepreneurial intention: Mexico and Spain - Tapia Mejia, Erik; Pico Gonzalez, Beatriz (Revista Venezolana de Gerencia, 2023)
This paper analyzes the influence of creativity and disruptive innovation on entrepreneurial intention, considering the subjective social norms and personal attitude of the Theory of Reasoned Action, and through a structural equation model. The empirical study was applied to a sample of potential entrepreneurs in two countries: Mexico and Spain, to identify behavioral actions within the relationships of the proposed model. The main results obtained indicate that entrepreneurial intention is influenced by personal attitude towards entrepreneurship, which in turn is shaped by subjective social norms, and by the self-perception of their creative abilities. While Mexican present a greater relationship with the influence of entrepreneurial attitude on entrepreneurial intention, Spanish entrepreneurs are more confident in their creative abilities to develop their projects. It is concluded, that there is a need to develop communication and training campaigns aimed at Mexican and Spanish society to promote a better opinion of the entrepreneurial process as well as to generate actions to develop and include creativity and disruptive innovation as part of the entrepreneurial process.